Mashups by orchestration and widget-based personal environments : key challenges, solution strategies, and an application (2012)
Aims at exploring and addressing challenges regarding the realisation of widget-based user interface mashups and UI level integration, in terms of widget orchestration, and to assess their suitability for the creation of web-based personal environments. Defines mashups as a web page or application that uses and combines data, presentation or functionality from two or more sources to create new services and data sources to produce enriched results; main characteristics of a mashup are combination, visualization, and aggregation.\n
Keywords: INTERNET